THE ENTREPRENEURIAL COMPETENCE OF SCHOOL PRINCIPALS IN CREATING ENTREPRENEURIAL INNOVATION AT PUBLIC ELEMENTARY SCHOOLS IN CLUSTER II, NORTH ACEH REGENCY - Marliana, Marliana; Marsithah, Iis; Mukhlisuddin, Mukhlisuddin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to examine the entrepreneurial competencies of school principals in collaboration with the business world to create entrepreneurial innovations in public elementary schools, identify the entrepreneurial competencies of school principals in fostering student creativity to generate entrepreneurial innovations in public elementary schools, and analyze the entrepreneurial competencies of school principals in enhancing and realizing an entrepreneurial culture to create entrepreneurial innovations in the public elementary schools of Cluster II in North Aceh District. The focus of the study includes three elementary schools in North Aceh District, namely SDN 11 Lhoksukon, SDN 5 Lhoksukon, and SDN 1 Lhoksukon. The method used is descriptive qualitative with observation, interviews, and documentation techniques. The results show that school principals play a strategic role as drivers of innovation and creators of an entrepreneurial ecosystem. Through the school cooperative program, project-based activities to strengthen Pancasila student profiles (P5), mini markets, and collaboration with local SMEs and higher education institutions, the principal has successfully instilled entrepreneurial values such as independence, creativity, responsibility, and collaboration in students. The implementation of entrepreneurship education is integrated into thematic learning and daily student activities. Despite limited facilities, the three schools have demonstrated that an approach based on local potential and innovative leadership can foster an entrepreneurial culture from an early age. This finding reinforces that the entrepreneurial competence of school principals is key to creating contextual and sustainable educational innovations.